THE IMPORTANCE OF THE FUNCTIONING OF NATIONAL CULTURAL CENTERS IN UZBEKISTAN - Abdullayeva E.A. (Galaxy International Interdisciplinary Research Journal, 2023)
The article examines the influence of national cultural centers on various aspects of public life in Uzbekistan. The author emphasizes the importance of supporting and developing such institutions for the preservation of the cultural heritage of the people, the development of knowledge and skills related to national culture, the formation of interethnic tolerance and education of citizenship, as well as support for the local economy.